At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

3x + 2y = -1
4x + 2y = -6


Sagot :

Answer:

x = -5; y = 7

Step-by-step explanation:

We can use elimination to solve for x.

3x + 2y = -1

-1 (4x + 2y) = -1 (-6)

3x + 2y = -1

-4x -2y = 6

The 2y's cancel out and solving for x gives us x = -5.

Plugging -5 into any one of the equations gives us y = 7